Terceirização e terceirizados: um estudo sobre os impactos objetivos e subjetivos da terceirização sobre trabalhadores terceirizados que atuam no setor de limpeza em Escolas Estaduais no Município de Marília-SP - Cunha, Yuri Rodrigues da [UNESP] (2015)
The present dissertation aims to show the results of a master’s degree research whose objective was to investigate the subjective and objective impacts of outsourced hiring for workers under this contractual framework. This objective was investigated from the analysis of outsourced workers who work in the cleaning sector of State Schools in the district of Marília-SP. To achieve its objectives this research involved a theoretical and empirical study. In the theoretical aspect, we tried to understand the way the outsourcing phenomenon was spread in Brazil and in the public sector, analyzing thereby the historical context that culminated in the systematic adoption of these practices in the 90s, and also, analyzing texts and official notebooks to resize the way the public sector incorporated these practices. They were conducted, still under the theoretical aspects, studies of the companies’ administrators, sociologists of the work and syndical vision of that phenomenon. In the empirical and qualitative dimension of this research interviews took place through the support of the non-directing interviews. Therefore, it was possible to present that this kind of hiring reinforce the alienated and ideologically guided character of the work in the capitalist way of production, and that the people submitted daily to this contractual regime develop individual answers that enlarge that tendency.